Вплив концентрації іонів марганцю на люмінесцентні властивості кристалів YAlO3:MN - Жидачевський, Я. А. (Видавництво Національного університету “Львівська політехніка”, 2009)
Наведено результати дослідження люмінесцентних та термолюмінесцентних властивостей кристалів YAlO3:Mn із концентрацією іонів марганцю від 0.001 до 1 ат.%. Проведені дослідження дали змогу встановити, що для досягнення максимальної інтенсивності люмінесценції іонів Mn2+ в кристалі YAlO3 їх концентрація має бути порядку 0.1 ат.%. The work presents results of investigation of luminescence and thermoluminescence properties of YAlO3:Mn crystals with concentration of manganese ions from 0.001 to 1 at.%. The presented results allowed to establish that optimal concentration of manganese ions should be about 0.1 at.% in order to achieve a maximal intensity of luminescence of Mn2+ ions in YAlO3 crystal.
Influence of manganese concentration on the luminescence properties of yalo3:mn crystals
Keywords: люмінесцентні та термолюмінесцентні властивості кристалів; концентрація іонів; luminescence and thermoluminescence properties crystals; concentration ions